Surface properties and electronic band structure of 2D materials and thin films - Rahman, Kazi Sabrina (2024)
Two-dimensional (2D) semiconductors have the potential to drive significant advances in quantum science and technology. Atomically thin 2D materials play a dominant role in their electronic and optical properties due to their well controlled, tuneable and scalable band structure. This thesis explores the growth and electronic properties of GaSe layers on epitaxial graphene, with a focus on the evolution of the valence band maximum as the GaSe thickness increases at room temperature. The effects of oxygen and air exposure on monolayer GaSe, as well as the impact of thermal treatment, were systematically examined to understand the stability and electronic modifications induced by environmental interactions. Additionally, C60 monolayers and multilayer thin films were deposited on an Au(111) surface, and their electronic band structures were investigated. The findings provide valuable insights into the electronic behaviour of these materials, offering potential implications for future optoelectronic and nanotechnology applications. In this thesis, by utilizing angle-resolved photoelectron spectroscopy (ARPES), low energy electron diffraction (LEED) and scanning tunnelling microscopy (STM), we observed that atomically-thin layers of GaSe, grown by molecular beam epitaxy (MBE), align with the underlying graphene lattice in the layer plane. Our investigations reveal a transition from a ring-shaped to a parabolic valence band maximum as the GaSe layer thickness increases. In multilayers, the valence band maximum is centred at the Γ point, while in mono- and bilayers, it shifts along the ΓK direction, creating a ring-shaped maximum. This GaSe/graphene heterostructure features a charge dipole at the GaSe/graphene interface and a band structure that can be tuned based on the layer thickness. Our data shows that GaSe layers on graphene become n-type due to electron transfer from the n-type graphene, contrasting with the intrinsic p- type behaviour of GaSe. We investigated the stability of monolayer GaSe grown on epitaxial graphene in this thesis. GaSe demonstrates resilience to oxygen at room temperature, where the adsorption of O2 molecules on its surface effectively restores its original electronic properties. At temperatures above 450 ◦C, GaSe begins to react with oxygen, leading to the formation of gallium oxide (Ga2O3) with no selenium remaining. We further explore the effects of oxygen exposure, air exposure, and heat treatments on the electronic band structure of monolayer GaSe. While the band structure is preserved under these conditions, a notable shift towards the Fermi level indicates that the GaSe layer acts as an acceptor. Additionally, in the GaSe/graphene van der Waals heterostructure, the interaction between the two layers remains robust, highlighting the potential of this heterostructure for advanced device applications. Finally, we deposited C60 on an Au(111) surface via sublimation using a Knudsen cell (K-cell) to prepare C60 thin films adsorbed on the substrate. We employed angle-resolved photoelectron spectroscopy (ARPES) to investigate the band structure of the thin C60 film on Au(111), focusing on the delocalized π-like valence states. Specifically, we analyzed the highest occupied molecular orbital (HOMO) and the HOMO-1 states within the entire valence band structure of C60, a prototypical three-dimensional (3D) organic molecule. We found that the two frontier molecular orbitals, HOMO and HOMO-1, exhibit weak band dispersion, which we attribute to their pure π-orbital character that extends across adjacent molecules. In contrast, the sharper emission peaks at larger binding energies are attributed to σ orbitals, which remain localized on individual C60 molecules. This charge transfer leads to a bonding interaction between the molecule and the metal surface, often described as chemisorption. The electron density transferred to the C60 molecule stabilizes it on the surface, resulting in a stronger interaction compared to mere physisorption, which involves weaker van der Waals forces.